Literature Review: Psychological Therapy in People with Schizophrenia - Shierlyana Agna Putri; Made Diah Lestari (CV. Publikasi Indonesia, 2025)
Schizophrenia is a severe mental disorder that impacts thoughts, emotions, and behavior, and psychological therapy plays a crucial role in managing symptoms, enhancing quality of life, and supporting recovery. The purpose of this study was to explore various psychological therapy intervention approaches that are effective in treating schizophrenia. The research method used was a narrative literature review of articles found in the Google Scholar database. The results of this study show that there are more than five effective therapies used in schizophrenia patients. Overall, this study shows that cognitive remediation, or cognitive remediation, is a highly effective therapist-assisted intervention that aims to improve the cognitive functioning of individuals with schizophrenia, especially with regard to memory, attention, and problem-solving skills. The goal of cognitive remediation is to improve and strengthen impaired cognitive functioning in people suffering from mental health problems, such as schizophrenia